ANOMALI DEMOKRASI INDONESIA: Kontroversi Peningkatan Partisipasi Politik pada Pemilihan Kepala Daerah dalam masa Pandemi Covid-19 - Laode Harjudin; La Husein Zuada; Muhammad Ishak Syahadat (Journal Publicuho, 2023)
This study discusses the implementation of regional head elections in Indonesia which took place during the Covid-19 pandemic. The study focuses on explaining the high level of voter turnout when Covid-19 hit Indonesia in 2020 which exceeded the turnout rate in normal situations and contrary to the trend of declining global voter turnout. This research uses descriptive qualitative methods with secondary data obtained from official government institutions (especially the election commission and Ministry of Health), mass media both newspapers and other social media, as well as the results of research conducted by other researchers. The results showed that the high level of voter turnout during the Covid-19 pandemic was an anomaly of democracy in the midst of activity restrictions and the trend of declining global voter turnout. The high voter turnout during the Covid-19 pandemic was inversely proportional to the economic downturn and public confidence in government. This study found that the main factor for increasing voter turnout during the Covid-19 pandemic was the massive mobilization of social assistance funds from the government. Theoretically, this is a synthesis of the mobilization model and the general incentives model of participation in a pragmatic context.